EVALUATION OF CHANGES IN THE MOTIVES OF PHYSICAL CULTURE AND SPORTS AMONG STUDENTS DURING THE PERIOD OF SELF-ISOLATION - Grachev, A.S.; Egorov, D.E.; Kopeikina, E.N.; Sheplyakov, A.S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to assess the change in the motives for physical culture and sports among students during the pandemic. Methods and structure of the study. In February 2020, an online survey was conducted, which was based on the methodology of A.V. Shaboltas, adapted for physical education at the university. The study involved 1385 students of Belgorod universities (n=755 girls and n=630 boys). A second survey was conducted in late April - early May 2020. It was found that the distribution of motives of boys and girls before self-isolation was identical. Results and conclusions. During self-isolation, an increase in the indicators of the motive of emotional pleasure and social self-affirmation was noted. Moreover, in girls, the indicators of this motive significantly increased from 2.8±2.4 points to 3.6±2.3 points and moved from the last line of the rating of motives to the penultimate one. Thus, it was found that the self-isolation associated with Covid-19 and the limitations in self-expression that arose among students contributed to an increase in the significance of the motive of social self-assertion. Consequently, students have formed a desire to prove themselves, which is expressed in the fact that physical education classes and the successes achieved at the same time are considered and experienced from the point of view of personal prestige and respect from friends/acquaintances.